SIFAT PAPAN WOL KAYU DARI 12 JENIS KAYU HUTAN TANAMAN INDUSTRI - I M Sulastiningsih; Rozak Memed; Paribotro Sutigno (Jurnal Penelitian Hasil Hutan (Journal of Forest Products Research), 2017)
The results  of  laboratory  test  of  wood-wood board properties  made from  12 individual  wood species obtained  from West Java, Lampung  and East Nusa Tenggara province are reported  in this paper.  The properties tested  were board density, moisture  content,   thickness  reduction   due  to compression  and bending strength.